2021
DOI: 10.3390/antibiotics10091040
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Antibiotic Prescribing Trends in Outpatient Care: A Nationwide, Quasi-Experimental Approach

Abstract: Coronavirus disease 2019 (COVID-19) has spread globally and is currently having a damaging impact on nearly all countries in the world. The implementation of stringent measures to stop COVID-19 dissemination had an influence on healthcare services and associated procedures, possibly causing antibiotic consumption fluctuations. This paper aims to evaluate the immediate and long-term impact of the COVID-19 pandemic on antibiotic prescribing trends in outpatient care of the Portuguese public health sector, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
5
22
0
6
Order By: Relevance
“…Esta tendencia se detecta en otros países, como Reino Unido o Portugal 18 , 19 , con un sistema sanitario parecido al nuestro y en otros continentes 20 , 21 , 22 . En un estudio del ámbito de AP 18 , la prescripción se redujo un 15,48% en el periodo de abril a agosto de 2020 respecto al mismo periodo de 2019, aunque, teniendo en cuenta el descenso experimentado en el número de consultas, consideran que el número de prescripciones fue un 6,71% mayor que el esperado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esta tendencia se detecta en otros países, como Reino Unido o Portugal 18 , 19 , con un sistema sanitario parecido al nuestro y en otros continentes 20 , 21 , 22 . En un estudio del ámbito de AP 18 , la prescripción se redujo un 15,48% en el periodo de abril a agosto de 2020 respecto al mismo periodo de 2019, aunque, teniendo en cuenta el descenso experimentado en el número de consultas, consideran que el número de prescripciones fue un 6,71% mayor que el esperado.…”
Section: Discussionunclassified
“…Además, esa reducción influye de forma importante en la evolución de la tasa de consumo anual durante 2014-2020. Este comportamiento del consumo de antibióticos en el periodo de pandemia se describe también en estudios de otros países 18 , 19 , 20 , 21 , 22 , y puede tener relación con cambios cuantitativos y cualitativos en la accesibilidad, en el perfil epidemiológico de las infecciones respiratorias, y en la propia práctica profesional.…”
Section: Discussionunclassified
“…Importantly, this may lead to higher resistance potential. Antibiotic selection pressure [ 34 , 35 ] would increase the incidence of multidrug-resistant organisms. Thirteen bacteria have been identified as causing a secondary infection to SARS-CoV-2, where it may lead to increased mortality and morbidity for COVID-19 patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from primary care in England have shown an overall decrease in antibiotic prescribing during 2020 compared to pre-pandemic [18][19][20][21][22][23], with similar trends identified in Scotland [24], Northern Ireland [25] and other countries [26][27][28][29]. However, one study on UK data noted an initial increase in antibiotic prescribing in March 2020 before prescribing levels dropped below those expected (with the lowest rate in May) [20].…”
Section: Introductionmentioning
confidence: 86%